2018
DOI: 10.4103/jfcm.jfcm_98_17
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of Saudi medical students towards complementary and alternative medicine

Abstract: BACKGROUND:Alternative medicine is defined as medical therapies that are not regarded as orthodox by the medical profession. The teaching of complementary and alternative medicine (CAM) in medical schools is becoming prevalent worldwide. Only a few studies have been done to assess medical students' attitude toward CAM and the need for CAM courses.MATERIALS AND METHODS:An observational, descriptive, cross-sectional study was conducted on medical students in two universities, King Saud (KSU) and Majmaah (MU) med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…On the other hand, healthcare workers (HCWs) who studied modern medicine had limited exposure to this subject as part of the course curriculum, and most HCWs lack training in this branch of medicine unless out of self-interest (Albadr et al, 2018;Clement et al, 2005). In such cases, HCWs show interest if they are supported by quality knowledge and guidelines (Hilal and Hilal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, healthcare workers (HCWs) who studied modern medicine had limited exposure to this subject as part of the course curriculum, and most HCWs lack training in this branch of medicine unless out of self-interest (Albadr et al, 2018;Clement et al, 2005). In such cases, HCWs show interest if they are supported by quality knowledge and guidelines (Hilal and Hilal, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…About 80% of the population in Arab societies relies on herbal medicines for the prevention and treatment of illness [6]. For instance, in Egypt, 37% of the population reported using herbal medicines [7], while, in Saudi Arabia, a higher proportion of the population (73%) have used herbal medicines [8]. In Jordan, herbal medicine has maintained popularity as a result of historical, cultural, and psychosocial factors [9].…”
Section: Introductionmentioning
confidence: 99%
“…There have been a rising number of studies investigating medical students’ knowledge and attitude regarding CAM in recent years. For example, two recent studies from Saudi Arabia that assessed knowledge and attitude regarding CAM among medical students [22, 23] concluded that there was a knowledge gap regarding CAM among students, despite their positive attitude towards the topic. Another study conducted at two universities in the United States investigated the views of medical students and students in other health-care professions on CAM [24] and reported that medical students received the least amount of education about CAM and doubted the usefulness of CAM the most among all health professions students.…”
Section: Introductionmentioning
confidence: 99%